The Role Of Brand Image And Quality Services Towards Customer Trust And Satisfaction Of Private Commercial Banks In Lamongan - Danny Mahendra; Abid Muhtarom; Sugeng Dwi Hartantyo (Sean Institute, 2024)
Customer satisfaction is important in the business world, especially in the service sector (Khaliq, 2018). Most of the literature considers providing quality services as an important strategy for the survival of companies, in this case private commercial banks. Moreover, private banks must be able to compete with state-owned banks and foreign banks. Apart from customer satisfaction, commercial banks also run a trust business . Trust in this case is a good relationship between the bank and its customers (Suwarman, 2013; Sangadji & Sopiah, 2013). This research is a type of quantitative research with Partial Least Square (PLS) statistical analysis. Data was obtained through a survey with a research instrument in the form of a questionnaire of 112 respondents. From the results of this research, results were obtained which stated that the variables Brand Image and Service Quality had a significant positive effect on Customer Satisfaction and Trust in private commercial banks in Lamongan.